PENGARUH SIKAP, DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA AKUNTASI UNIVERSITAS PAMULANG - RIFKHAN RIFKHAN (Universitas Pamulang, 2017)
The purpose of this research is to examine the effect of attitude and motivation level on student entrepreneurship interest of Accounting Study Pamulang University. The research was conducted by using descriptive and verifikatif quantitative method. The population in this study is the 8th grader of Accounting Study Program S1 Pamulang University. The sample in this research is 312 respondents. Sampling technique in this research is done by sampling technique. Data type is primary data and secondary data. Methods of data collection using questionnaires. The analysis technique used is multiple regression test, multiple correlation test, and verifikatif analysis among variables. The result of this research stated that the attitude does not have an effect on entrepreneurship interest and motivation influence to entrepreneurship interest, so it can be concluded that attitude has no positive and insignificant influence to entrepreneurship interest and motivation have positive and significant influence to entrepreneur interest.